2012
DOI: 10.1016/j.cell.2012.04.042
|View full text |Cite
|
Sign up to set email alerts
|

A CXCL1 Paracrine Network Links Cancer Chemoresistance and Metastasis

Abstract: Metastasis and chemoresistance in cancer are linked phenomena but the molecular basis for this link is unknown. We uncovered a network of paracrine signals between carcinoma, myeloid and endothelial cells that drives both processes in breast cancer. Cancer cells that overexpress CXCL1 and 2 by transcriptional hyperactivation or 4q21 amplification are primed for survival in metastatic sites. CXCL1/2 attract CD11b+Gr1+ myeloid cells into the tumor, which produce chemokines including S100A8/9 that enhance cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
861
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 963 publications
(905 citation statements)
references
References 49 publications
39
861
5
Order By: Relevance
“…For example, depletion of Gr1 + myeloid cells or Ly6G + neutrophils reduced the anti-cancer efficacy of cyclophosphamide and doxorubicin in tumor inoculation models 187,188 . These data contrast to the improved tumor inhibition achieved by combining CXCR2 blockade with doxorubicin, cyclophosphamide or docetaxel in xenograft and de novo tumorigenesis mouse models 58,132 . Moreover, some chemotherapeutics, such as gemcitabine and 5-fluorouracil, directly reduce the viability and/or change the functionality of myeloid cells, which then influences the anti-cancer efficacy of these drugs.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…For example, depletion of Gr1 + myeloid cells or Ly6G + neutrophils reduced the anti-cancer efficacy of cyclophosphamide and doxorubicin in tumor inoculation models 187,188 . These data contrast to the improved tumor inhibition achieved by combining CXCR2 blockade with doxorubicin, cyclophosphamide or docetaxel in xenograft and de novo tumorigenesis mouse models 58,132 . Moreover, some chemotherapeutics, such as gemcitabine and 5-fluorouracil, directly reduce the viability and/or change the functionality of myeloid cells, which then influences the anti-cancer efficacy of these drugs.…”
contrasting
confidence: 66%
“…These factors override retention signals in the bone marrow, facilitating neutrophil egress and elevated numbers of circulating neutrophils (Figure 2). Cancer cells themselves produce these cytokines 27,28,58 , but stromal and immune cells can also contribute to their elevated expression in tumor-bearing mice. For example, tumor-associated macrophages are a wellknown source of IL-1β 59 .…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to IL‐6, IL‐8, and IL‐1β, another ZEB1‐regulated cytokine, G‐CSF/CSF3, also enhances the accumulation of MDSCs (Talmadge and Gabrilovich, 2013). ZEB1 also regulates the expression of the chemokines CXCL1 and CXCL5, which are the ligands for the CXCR2 receptor, and increases the infiltration of PMN‐MDSCs (Acharyya et al ., 2012; Katoh et al ., 2013; Toh et al ., 2011). Although the present study showed no additional effect of ZEB1 on tumor progression or on the metastasis of 4T1 cells, which may be due to the aggressive nature of the parental 4T1 cells, these observations suggest that inflammatory cytokines induced by ZEB1 play critical roles in the progression of cancer in a context‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…There has been extensive research in recent years focusing on the roles of various cells of innate and adaptive immunity that facilitate solid tumour growth by regulating angiogenesis, invasion, and metastasis [4][5][6][7][8], and more recently in regulating the response of tumours to cytotoxic therapy [9][10][11]. Notably lacking from these studies have been in-depth analyses focusing on the role of cancer-associated fibroblasts (CAFs) as inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%